2019
DOI: 10.1177/0954405419838956
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of laser peening and its impact on hydrogen embrittlement of titanium alloys

Abstract: Many efforts have been made to understand the effects of hydrogen on titanium alloys, resulting in an abundance of theoretical models and papers. Titanium alloys are crucial advanced materials that provide an excellent combination of a high strength-to-weight ratio and good corrosion behaviour even though they are reasonable to corrosion attack. Titanium alloys are susceptible to hydrogen embrittlement when comes into contact with hydrogen, and galvanic pair with an active metal current, or the pH is greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 258 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…Improved fatigue resistance, reduced stress corrosion cracking [73][74][75] Aerospace, automotive, medical, and nuclear industries [76] Improved surface properties, deeper layer of compressive residual stress [77] Limited to small areas, expensive [78] Submerged laser peening Improved fatigue resistance, reduced stress corrosion cracking [79,80] Aerospace, automotive, medical, and nuclear industries Reduced thermal damage to surface, deeper layer of compressive residual stress [81] Limited to submerged surfaces, requires specialized equipment [82] Surfi-Sculpt processing (three-dimensional laser surface modification)…”
Section: Laser Surface Modification Methodsmentioning
confidence: 99%
“…Improved fatigue resistance, reduced stress corrosion cracking [73][74][75] Aerospace, automotive, medical, and nuclear industries [76] Improved surface properties, deeper layer of compressive residual stress [77] Limited to small areas, expensive [78] Submerged laser peening Improved fatigue resistance, reduced stress corrosion cracking [79,80] Aerospace, automotive, medical, and nuclear industries Reduced thermal damage to surface, deeper layer of compressive residual stress [81] Limited to submerged surfaces, requires specialized equipment [82] Surfi-Sculpt processing (three-dimensional laser surface modification)…”
Section: Laser Surface Modification Methodsmentioning
confidence: 99%
“…The current density application condition for the hydrogen embrittlement research was 10 mA cm −2 . [11][12][13] In addition, hydrogen embrittlement was carried out in a 2 N H 2 SO 4 + 1 g l −1 Na 2 HAsO 4 ·7H 2 O electrolyte at RT for 3 and 6 h. Hydrogen embrittlement is a phenomenon caused by atomic hydrogen (H + ), and molecular hydrogen (H) can hardly penetrate aluminum alloys. 14) Therefore, the experimental solution contained arsenic (As), a hydrogen recombination inhibitor, to promote hydrogen embrittlement.…”
Section: Hydrogen Embrittlementmentioning
confidence: 99%
“…However, research has shown that the alloys' overall properties depend on the degree of impurity they contained, which adversely affects their plasticity [ 23 , 24 , 25 ]. Titanium alloys undergo plastic deformation when hydrogen, carbon, oxygen, and nitrogen are present [ 26 , 27 ]. In general, alloying elements play a crucial role in stabilizing its α or β phase [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%